2015
DOI: 10.1590/0102-33062015abb0084
|View full text |Cite
|
Sign up to set email alerts
|

Key factors affecting seed germination of Copaifera langsdorffii, a Neotropical tree

Abstract: In natural conditions biotic and abiotic factors interact, synergistically affecting seed germination. In this study, we experimentally simulated natural conditions that occur during seed dispersal that can affect the germination of Copaifera langsdorffii. Specifically we evaluated the effect of aril removal by different dispersal agents (birds and ants) and fire on germination. The seeds were submitted to the following treatments: Control (seeds placed to germinate with aril intact); Acid (simulation of passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Nevertheless, the number of dead seeds was lower than on the non-removal treatment, which suggests the importance of removing the sarcotesta of G. guidonia seeds in forest nurseries cultivating. Some studies conducted on other species showed improved germination on manually removed appendages compared to those not removed (Guimarães & Cogni, 2002;Passos & Oliveira, 2003;Christianini et al, 2007;Leal et al, 2007;Lima et al, 2013;Souza et al, 2015). These differences may have resulted from disinhibition effect induced by the aril or pulp removal, which is frequently higher than seed scarification and occurs in several species (Robertson et al, 2006).…”
Section: /7mentioning
confidence: 99%
“…Nevertheless, the number of dead seeds was lower than on the non-removal treatment, which suggests the importance of removing the sarcotesta of G. guidonia seeds in forest nurseries cultivating. Some studies conducted on other species showed improved germination on manually removed appendages compared to those not removed (Guimarães & Cogni, 2002;Passos & Oliveira, 2003;Christianini et al, 2007;Leal et al, 2007;Lima et al, 2013;Souza et al, 2015). These differences may have resulted from disinhibition effect induced by the aril or pulp removal, which is frequently higher than seed scarification and occurs in several species (Robertson et al, 2006).…”
Section: /7mentioning
confidence: 99%
“…This experimental design assumed each seed with their specific mass to be a statistically independent experimental unit, thus permitting comparisons of seed germinability among treatments (see Warton & Hui 2011;Souza & Fagundes 2014). Before sowing, all seeds were subjected to disinfection by immersion in a 1 % sodium hypochlorite solution for two minutes (Souza et al 2015). The humidity of the germination substrate was maintained daily by adding three milliliters of distilled water to each germination cell.…”
Section: Intraspecific Variation In Seed Size and Light Intensity Affmentioning
confidence: 99%
“…It has a large distribution range in South America, which includes areas from northern Argentina, southern Bolivia and the Brazilian Savanna (OLIVEIRA-FILHO; RATTER, 1995;RATTER et al, 2003). Moreover, the seed tolerance to high temperatures (SOUZA et al, 2015), its zoochoric dispersal (SEBBENN et al, 2011) and its shade tolerance (AQUINO; BARBOSA, 2009) corroborates with its wide geographic distribution.…”
Section: Occurrence Species Areasmentioning
confidence: 69%